Allocating weightage to sustainability criteria's for performance assessment of group housing developments: Using fuzzy analytic hierarchy process. (15th April 2023) - Bhyan, Parul; Shrivastava, Bhavna; Kumar, Nand
Abstract: Sustainability assessment is a method to assess the effectiveness of sustainability performance. The construction industry largely acknowledges Green Building Rating Systems (GBRS) as a tool for evaluating sustainability performance. With an emphasis on group housing constructions in India, the present study created a methodology for evaluating sustainability performance. An in-depth analysis of the GBRS and published literature, followed by expert interviews, created a methodology with five building life cycle stages and fifteen criteria's focusing on sustainability. Stakeholder perception was collected, and the data was assessed using the Fuzzy Analytic Hierarchy Process, to determine the priority weight of sustainability criteria and sub-criteria (FAHP). The development of a comprehensive system to account for sustainability on both the intergenerational and intragenerational levels for sustainability assessment is required. This study serves to be the first study to develop a comprehensive sustainability assessment system specific to group housing in India throughout the building life cycle stages. Highlights: Manuscript emphasises importanat parameters unique to group housing developments. Mini Delphi technique "Estimate talk estimate" is used to extract parameters from the literature. Stakeholder perception survey is used to assess sustainability in group housing developments in India. Using the FAHP technique, a hierarchy tree was developed to evaluate the sustainability of group housing developments in India.